2021
DOI: 10.1186/s12969-021-00494-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α2 gene polymorphism is a risk factor of coronary artery lesions in Chinese children with Kawasaki disease

Abstract: Background Kawasaki disease (KD) is a systemic vasculitis, and the formation of coronary artery lesions(CAL) is its most common sequela. Both genetic and environmental factors are considered to be important factors of in KD. Integrin α2 (ITGA2) is a transmembrane receptor that is associated with susceptibility to several diseases, but its relevance to KD with CAL is unclear. Methods We genotyped ITGA2 rs1126643 in 785 KD patients with the CAL and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
0
1
Order By: Relevance
“…Обнаружен значительно повышенный риск БК с ПКА, связанный с генотипами ITGA2 rs1126643 (CT против CC, отношение шансов (ОШ) =1,57, доверительный интервал (ДИ): 1,16-2,12, p=0,0032; CT/TT vs CC: ОШ =1,49, ДИ: 1,12-2,00, p=0,0068; T vs C: ОШ =1,66, ДИ: 1,16-2,51, p=0,0165). Выявлено также, что носители генотипа CT/TT имели значительный риск БК с восприимчивостью к ПКА у детей в возрасте до 60 мес., а генотип CT/TT был достоверно связан с повышенным риском образования чешуек и ПКА по сравнению с генотипом CC [9]. Мутация C807 в гене ITGA2 связана с риском раннего инфаркта миокарда, ишемического инсульта, эмболии, тромбоза после ангиопластики и стентирования коронарных артерий.…”
Section: ключевые моменты Key Messagesunclassified
“…Обнаружен значительно повышенный риск БК с ПКА, связанный с генотипами ITGA2 rs1126643 (CT против CC, отношение шансов (ОШ) =1,57, доверительный интервал (ДИ): 1,16-2,12, p=0,0032; CT/TT vs CC: ОШ =1,49, ДИ: 1,12-2,00, p=0,0068; T vs C: ОШ =1,66, ДИ: 1,16-2,51, p=0,0165). Выявлено также, что носители генотипа CT/TT имели значительный риск БК с восприимчивостью к ПКА у детей в возрасте до 60 мес., а генотип CT/TT был достоверно связан с повышенным риском образования чешуек и ПКА по сравнению с генотипом CC [9]. Мутация C807 в гене ITGA2 связана с риском раннего инфаркта миокарда, ишемического инсульта, эмболии, тромбоза после ангиопластики и стентирования коронарных артерий.…”
Section: ключевые моменты Key Messagesunclassified
“…ITGA2 gene polymorphism is one of the important factors affecting CAL in children with KD combined with CAL, and the risk of KD combined with CAL associated with ITGA2rs1126643 genotype is significantly increased.Stratified analysis showed that ITGA2rs1126643 could inhibit the formation of coronary artery small aneurysms (SCAL) and coronary artery medium aneurysms (MCAL) induced by KD, among which, compared with rs1126643CC genotype, the harmful effects of CT/TT variant genotype were more obvious in children ≤60 months and men [31 ] .…”
Section: Integrin α2 (Itga2)mentioning
confidence: 99%